Republic of Congo : First Review under the Three-year Extended Credit Facility Arrangement, Requests for Modification of Performance Criteria, and Financing Assurances Review-Press Release; Staff Report; and Statement by the Executive Director for the Republic of Congo. - International Monetary Fund. African Dept. (Washington, D.C. : International Monetary Fund, 2022)
Economic recovery is gaining momentum but remains fragile amid the on-going COVID-19 pandemic and Ukraine war's ripple effects. Despite oil exports benefiting from high oil prices, the war's impact on prices of food and other essentials weighs on households and businesses. Over the medium term, challenges from climate change and the global transition to low-carbon economies persist. In this context, steadfast reform implementation is needed to reduce fragility through job creation and higher incomes. Debt remains sustainable but is classified as "in distress" due to arrears; a financing assurances review was conducted. Debt vulnerabilities to negative oil price shocks remain. A three-year Extended Credit Facility (ECF) arrangement in the amount of SDR 324 million (200 percent of quota) was approved by the IMF Executive Board on January 21, 2022.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: International Agreements and Observance; International Organizations; Monetary Policy; Congo, Republic of